Criteria of cyclic compactness of the sets from Lp - spaces, associated with vector measure - Rakhimov, Akmal; Chilin, Vladimir; Rakhimov, Abdumalik A. (American Institute of Physics, 2013)
We study the conditional expectations in the Lp-modules associated with a partition of unity of a Boolean algebra. Cyclic compactness criteria of the subsets of Lp found in terms of convergent nets of conditional expectations.